PERAN UNITED NATIONS MISSION IN SOUTH SUDAN (UNMISS) DALAM MENANGANI KRISIS HEWAN TERNAK DI SUDAN SELATAN - Ash Shidqi, Kachfi; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research analyzes the role of United Nations Mission in South Sudan (UNMISS) in solving cattle crisis in South Sudan. Cattles are known to have exceptionally high value both figuratively and literally in South Sudan, and the crisis that was caused mainly by Cattle Raiding and the escalation of civil conflict has made an extremely massive amount of casualties to this country and its people. The civil war, involving the government and the opposition, have caused the inclusion of a large amount of weaponry to the country which in turn made the conflict and situation deadlier than ever. With this situation, the United Nations (UN) efforts in founding UNMISS is a topic that needs to be researched to understand the mechanism, support both domestically and internationally, and its result in solving the crisis that was happening. This qualitative research analyzes the problem using the internasional organization theory of Clive Archer. Datas that arerelevant are relevant are taken from documents, internationa and local journal, books, official reports, newspaper, etc. The result shows that UNMISS has succeeded in doing its role as an actor in solving the ongoing crisis. These efforts that was done by UNMISS include security mandate, the ratification of Marial Bai Agreement, which also include collaboration with local government and people, which ultimately is a big part of implementing reconciliation of conflicts between ethnic groups. It can be seen from the result that Cattle Raidings and crisis has steadily dropped compared to when the civil war started with all kinds of community with the government being united to obey UNMISS policies and the organization’s effort which mostly succeeded in controlling armed conflicts in the country. Keywords: UNMISS, Cattle Raiding, Cattle, South Sudan